Strategies to load curcumin into poly(2-hydroxyethyl methacrylate)-based disks to increase controlled release time for intraocular lenses - Rayner, Christopher A.; Wells, Laura A. (CMBES Proceedings, 2024)
I. Introduction The Canadian Council of the Blind estimates that 3.7 million Canadians were living with cataracts in 2019 [1]. Treatment involves replacing the diseased lens with a prosthetic intraocular lens (IOL). After surgery, patients apply eye drops with anti-inflammatories and antibiotics but the drugs’ low retention times on the eye and poor diffusion through the eye limit their effectiveness. Furthermore, reactive oxygen species can promote epithelial to mesenchymal transition in lens epithelial cells contributing to posterior capsule opacification [2]. Curcumin inhibits these transitions at low concentrations of 10 μM [3], but easily degrades and is hydrophobic making ocular delivery challenging [4]. We hypothesized solvent-based loading strategies would allow high amounts of curcumin to be loaded into IOL materials to protect the curcumin and allow controlled release over months. II. Materials and Methods Hydrogel disks were made by polymerizing 71 mol% 2-hydroxyethyl methacrylate, 7 mol% methyl methacrylate, 21 mol% acrylamide, and 1 mol% ethylene glycol dimethacrylate through free radical polymerization (Irgacure-1173 and UV light). The disks were dried and loaded with curcumin using a variety of acetone:water ratios, concentrations, and incubation times, and then dried to remove solvents. After reswelling, each disk was incubated in 3 mL of phosphate buffered saline (PBS) and periodically, solutions were replaced with fresh PBS and the releasate measured spectrophotometrically. At the conclusion of the release studies, 2,2-diphenyl-1-picrylhydrazyl (DPPH•) assays were done on the remaining encapsulated curcumin (after its extraction) and compared to fresh solutions. III. Results and Discussion The resulting disks were similar to IOLs with a water content of 45%, transmittance of 90% (375-700 nm), and refractive index of 1.42 ± 0.002. Incubation of disks with curcumin solutions of high acetone:water ratios enabled high loading of curcumin without damage to the disks. Curcumin appeared to slightly reduce disk swelling, and Figure 1 shows its extended release for over 60 days with potential for greater than 90 days (three months) of release based on assessments of the remaining curcumin content, longer than many ocular delivery systems loaded using soaking techniques which deliver over days or weeks [5]. Release rates of 0.0029 ± 0.0002 μmol/day (Loading Ratio 1) and 0.0027 ± 0.0003 μmol/day (Loading Ratio 2) were observed in the release studies from Fig. 1 after 25 days (p < 0.05). Precipitate found on the disks suggest dissolution was the mechanism of release, protecting the curcumin. The curcumin remaining in the hydrogel disks after 60 days was measured to have the same scavenging capability to fresh solutions of matched concentration (p > 0.05). Curcumin typically degrades quickly in solution (60% degradation in one hour with light exposure) [4] but the disks protected the curcumin over the lengthy release studies. <img src="https://proceedings.cmbes.ca/public/site/images/carayner/release-of-curcumin-into-pbs-ph-7.4-37c-sd-n3.jpg" alt="Fig. 1 Release of curcumin into PBS (pH 7.4, 37°C) (± 1 SD, n=3)." width="629" height="366"> Fig. 1 Release of curcumin into PBS (pH 7.4, 37°C) (± 1 SD, n=3). IV. Conclusion Loading solutions with mixtures of acetone and water enabled the high loading of curcumin into the hydrogel disks. After 25 days, its release was independent of loading and continued past two months. Curcumin loaded into poly(2-hydroxyethyl methacrylate)-based disks maintain activity upon release over extended periods of time. REFERENCES CCB, “The cost of vision loss and blindness in Canada”, Deloitte Access Economics, Sydney, AUS, May 2021. Kubo, et al., “Roles of TGF β and FGF Signals in the Lens: Tropomyosin Regulation for Posterior Capsule Opacity”, Int. J. Mol. Sci., vol. 19, no. 10, p. 3093, 2018. Liu, et al., “Curcumin Inhibits Proliferation and Epithelial-Mesenchymal Transition in Lens Epithelial Cells through Multiple Pathways”, BioMed Res. Int., vol. 2020, no. 6061894, 2020. Appendino, et al., “Shedding light on curcumin stability”, Fitoterapia, vol. 156, no. 105084, 2022. Topete, et al., “Intraocular lenses as drug delivery devices”, Int. J. Pharm., vol. 602, no. 120613, 2021.